A Comprehensive Approach to Unilateral Cleft Lip and Palate Management through Presurgical Nasoalveolar Molding and Surgical Repair in a Neonate - Lucky Yadav; Navraj Mattu; Pravesh Mehra; Pooja Jain (Wolters Kluwer Medknow Publications, 2024)
This case report details the successful application of nasoalveolar molding (NAM) in a 4-day-old neonate with a complete unilateral cleft lip and palate, showcasing a comprehensive treatment approach involving presurgical NAM and subsequent surgical repair. The NAM technique, pioneered by Barry H. Grayson, utilizes a specialized appliance to shape the alveolar ridge and nasal cartilage concurrently. The case demonstrates favorable outcomes, with the alveolar segments brought closer to normalcy after approximately 4 months of NAM. The patient underwent further surgical repair, as per the protocol emphasizing the interdisciplinary approach in cleft management.